2014
DOI: 10.1586/17474124.2014.881716
|View full text |Cite
|
Sign up to set email alerts
|

Atopy and the gastrointestinal tract – a review of a common association in unexplained gastrointestinal disease

Abstract: In addition to diseases conventionally associated with atopy there is increasing recognition that atopy is also linked to a spectrum of gastrointestinal (GI) manifestations, including food allergy, primary eosinophilic GI disease, functional gastrointestinal disorders, gluten interactions, gastroesophageal reflux disease and inflammatory bowel disease. These associations may be underpinned by shared genetic susceptibilities, initiation of related immune pathways and common patterns of exposure to environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 118 publications
4
34
0
8
Order By: Relevance
“…In this same group, atopic conditions were also found in excess among all FGID groups considered when compared with controls [42]. This association may be explained by a shared genetic susceptibility, or common disruption of the microbiome and similar immunological disorders in these conditions [43]. A study from the USA showed similar findings, in that adults with atopic symptoms report a high prevalence of IBS, suggesting a link between atopy and IBS [44].…”
Section: Fgids Autoimmune Diseases and Atopysupporting
confidence: 52%
“…In this same group, atopic conditions were also found in excess among all FGID groups considered when compared with controls [42]. This association may be explained by a shared genetic susceptibility, or common disruption of the microbiome and similar immunological disorders in these conditions [43]. A study from the USA showed similar findings, in that adults with atopic symptoms report a high prevalence of IBS, suggesting a link between atopy and IBS [44].…”
Section: Fgids Autoimmune Diseases and Atopysupporting
confidence: 52%
“…2). 48 In some patients, this process can lead to tissue injury and symptoms, whereas in others eosinophils may be protective and promote healing. An inflamed duodenum may be sensitive to acid and induce reflex responses and cytokine release that alter gastroduodenal function and result in mealrelated symptoms.…”
mentioning
confidence: 99%
“…An IgE-mediated immune reaction might be the bridge under this association, supported by the positive correlation among serum total IgE, HDM-specific IgE, and abdominal bloating in atopic patients. As is known, dysregulated immune activation on the epithelial barrier surfaces is common in both allergy and IBS [17]. Lillestol et al [16] reported earlier that elevated numbers of IgEpositive cells in duodenal mucosa were found in patients with atopy compared to nonatopic patients.…”
Section: Discussionmentioning
confidence: 97%